INNOVATION IN MAKING AROMATHERAPY CANDLES BASED ON CITRONELLA AS AN ENVIROMENTALLY FRENDLY MOSQUITO REPELLENT - Yuniar Sari, Niken; Amin , Ismi; Indri Saputri, Lutfiani; Minarni, Sri; Oktaviani Marito Siahaan, Alisia; Raja Gukguk, Christina; Zahratun Nisa, Keisya; Mardinah, Shaffa; Waldain, Berry; Alif Ramadhan, Ichwanul; Uyuni, Wardatul; Oktaviani Azhar, Nabila; Erikawati, Febby (Jurusan Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
Dengue Hemorrhagic Fever (DHF) remains a significant public health problem with an increasing incidence rate each year. Prevention of mosquito bites can be carried out through various methods, one of which is the utilization of natural ingredients as an alternative mosquito repellent. This community service program aimed to improve the knowledge and skills of residents in utilizing lemongrass (Cymbopogon citratus) as the main ingredient for producing eco-friendly aromatherapy candles as mosquito repellents. The methods used included health education, demonstration of candle-making, and evaluation through pre-test and post-test. The activity was conducted in RW 08 with a total of 25 participants. The results showed an increase in participants' knowledge, where before the intervention only 40% were in the good to excellent category, rising to 80% after the intervention. Participants demonstrated enthusiasm and were able to practice the candle-making process independently. In conclusion, this program effectively enhanced community knowledge and provided practical skills in utilizing natural ingredients as an alternative method to prevent mosquito bites and reduce DHF transmission.